THE ROLE OF CLINIC, LABORATORY AND INSTRUMENTAL METHODS IN DIAGNOSTICS OF NON-ALCOHOLIC STEATO-HEPATITIS - Filippova, A.Yu. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Different methods of diagnostics of non-alcogolic steatohepatitis were analyzed. Clinical and biochemical examinations in diagnostics of steatosis must have supplementary role in addition to ultrasound examinations, echocontrol punctional biopsy of liver, morphological investigations of hepar tissue. Ultrasound examination of abdominal cavity organs in case of impossibility of morphological investigation of hepar can be the single method for diagnostics of steatosis. Prediction of non-alcogolic steatogepatitis depends on expressiveness of histological changes. Diagnostics of non-alcogolic steatohepatitis must be based on combination of several features: histological characteristic, ultrasound examination, absence of alcohol abuse and data of examinations, which let us exclude other chronic hepar diseases.